Contamination by chlorinated pesticides, PCBs and PBDEs in Atlantic spotted dolphin (Stenella frontalis) in western South Atlantic - Leonel, Juliana; Taniguchi, Satie; Sasaki, Dalton K.; Cascaes, Mauro J.; Dias, Patrick S.; Botta, Silvina; Santos, Marcos C. de O. [UNESP]; Montone, Rosalinda C. (Pergamon-Elsevier B.V. Ltd, 2012)
Chlorinated pesticides, PCBs and PBDEs were analysed in nine blubber samples of Atlantic spotted dolphins, Stenella frontalis, incidentally captured during fishing operations in southern and southeastern Brazil between 2005 and 2007. The majority of compounds analysed were detected, suggesting widespread contamination over the region. Although the samples came from a location far from main coastal industrial areas, the results revealed an influence from such sources. Therefore, levels of PCBs (774-23659 ng g(-1) lipid wt.) and PBDEs (23-1326 ng g(-1) lipid wt.) detected seem to be related to the movement of individuals throughout near-shore and offshore waters. The sample from a lactating female exhibited a lower level of contamination and a distinct pattern, indicating selective transfer favouring less lipophilic compounds. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Chlorinated pesticides; PCBs; PBDEs; Atlantic spotted dolphin; Stenella frontalis; Brazilian coast